Examination of disease severity in systemic vasculitis from the novel perspective of damage using the vasculitis damage index (VDI). - Exley, A; Bacon, P; Luqmani, R; Kitas, G; Carruthers, D; Moots, R (1998)
Assessment of disease severity in systemic vasculitis encompasses mortality, which is now uncommon, and morbidity, which is increasing in significance. Morbidity includes permanent scars or damage, an evolving concept offering a novel perspective which may be particularly valuable in chronic disease. We have developed a method for assessing damage in systemic vasculitis, but the relationship between damage and disease severity was unknown. Therefore, we examined whether the number of items of damage or the pattern of damage varied with the severity of systemic vasculitis. We established the characteristics of severe disease by examining fatal vasculitis as an example of the most severe disease possible. We then showed that more damage occurred in fatal vasculitis, more systems were damaged, and critical damage akin to organ failure was more common in fatal than non-fatal vasculitis. These observations were reproduced in specific diagnostic groups, namely classical Wegener's granulomatosis and systemic rheumatoid vasculitis. Thus, severe disease was characterized by many items of damage, multisystem damage and critical damage. This pattern of damage was also seen in a subgroup of patients with non-fatal vasculitis, who also have severe disease.